America's Safest City: Delinquency and Modernity in Suburbia - Singer, Simon I. (New perspectives in crime, deviance, and law series, 2014)
Since the mid-1990s, the fast-growing suburb of Amherst, NY has been voted by numerous publications as one of the safest places to live in America. Yet, like many of America's seemingly idyllic suburbs, Amherst is by no means without crime-especially when it comes to adolescents. In America's Safest City, noted juvenile justice scholar Simon I. Singer uses the types of delinquency seen in Amherst as a case study illuminating the roots of juvenile offending and deviance in modern society. If we are to understand delinquency, Singer argues, we must understand it not just in impoverished areas